Human-Associated Methicillin-Resistant Staphylococcus aureus Clonal Complex 80 Isolated from Cattle and Aquatic Environments - Khuliso Ramaite; Mutshiene Deogratias Ekwanzala; John Barr Dewar; Maggy Ndombo Benteke Momba (MDPI AG, 2021)
Background: Human-associated methicillin-resistant Staphylococcus aureus (HA-MRSA) has mainly been reported in South African pig and chicken farms. The prevalence of antibiotic-resistant genes (ARGs), virulence factors (VFs), and multilocus sequence types (MLSTs) associated with HA-MRSA in cattle farms has not been reported. Consequently, this study characterised LA-MRSA and its spread from cattle farms into the environment. Method: Husbandry soil (HS), nearby river water (NRW), animal manure (AM) and animal drinking water (ADW) were collected on and around a cattle farm. Presumptive MRSA isolates were identified from these samples using CHROMagar media and genotyped as MRSA sequence types (STs), selected ARGs, and VFs, using polymerase chain reaction. An MLST-based dendrogram was generated to link the farm MRSA strains with those in a nearby river. Results: The prevalence of MRSA was 30.61% for HS, 28.57% for ADW, 22.44% for NRW, and 10.20% for AM. Isolates from HS harboured the highest number of resistant genes, with 100% for mecA, 91.66% for ermA, and 58.33% for blaZ. However, no ermC or tetM genes were detected. MRSA isolates from AM harboured the lowest number of resistant genes. Only sec and seq enterotoxins were found in all the assessed MRSA isolates. MRSA from the farm revealed six STs (ST80, ST728, ST1931, ST2030, ST3247, and ST5440); all of STs belonged to clonal complex 80 (CC80). An MLST-based dendrogram based on the concatenated sequences of MLST genes under the maximum likelihood criterion revealed four clades of amalgamated MRSA isolates from various livestock environmental matrices, including the NRW. Conclusion: The results suggest that livestock environmental matrices might be reservoirs of MRSA that could subsequently disseminate through runoff to pollute water resources. Therefore, continued surveillance of HA-MRSA in livestock environments is warranted.